A mathematical model of a bolted connection based on Florida contact theory to study the influence of the friction coefficient on structural performance. (May 2019) - Xu, Wenxiang; Liu, Zhifeng; Cheng, Qiang; Chen, Huaxiong; Zhao, Yongsheng; Li, Ying
Bolted joints are widely used for the mechanical assembly of engineering structures and friction coefficient of the contact surface of a bolted connection is the main factor that influences its structural performance. This article presents a mathematical model based on the Florida contact model to obtain the friction coefficient for the contact surface of a bolted joint. The pressure distribution function of the bolted joint is introduced into the mathematical model and elastic, elastic–plastic, and full plastic deformation of asperities at the microscale is also considered. By varying the peak height of asperities, an improved exponential distribution function was constructed. In addition, the proposed model was verified by comparing simulation results to experimental values obtained using a CETR UMT-5 high-precision ball-on-disk friction and wear tester. Then the theoretical friction coefficient was used in the finite element model of the bolted joint, and through numerical simulation, the state of the contact surface of the tightened bolted connection was analyzed. Increasing the friction coefficient was shown to improve the structural performance of the bolted joint. The results provide a theoretical basis for designing uniform preloading of bolted joints and reducing micro-slip at the joint interface.